Case report: Ultrasonographic findings of retroperitoneum and abdominal wall metastases of renal cell carcinoma with FH gene deletion - Zhang, Xuhui; Zhang, Yue; Li, Yongzhong; Shen, Pengfei; Liu, Zhenghua; Zeng, Hao; Zhang, Mengni; Chen, Ni; Yao, Jin; Huang, Rui; Cai, Diming (Frontiers in Oncology, 2022)
Renal cell carcinoma with FH gene deletion is a rare subtype of renal cell carcinoma. The ultrasonographic imaging of metastasis of renal cell carcinoma with FH gene deletion had few reported before. This case reported one of the features of metastasis of renal cell carcinoma with FH gene deletion of a male patient seven months after radical nephrectomy. He was diagnosed as renal malignant tumor before the operation and confirmed to be primary FH gene deficient renal cell carcinoma after radical nephrectomy in other hospital. Reexamination seven months after the operation indicated that multiple metastases all over the body were found; therefore, he came to our hospital for further diagnosis and therapy. The tumors have metastasized in lungs, bones, lymph nodes adjacent to the left reproductive vessels and external iliac vessels, retroperitoneum and abdominal wall so far by PET/CT or MRI. Ultrasonographic findings of masses in retroperitoneum and abdominal wall are fully discussed, which have been confirmed by biopsy and diagnosed as renal cell carcinoma with FH gene deletion by pathology.